Effects of high power ultrasound treatments on the phenolic, chromatic and aroma composition of young and aged red wine - Lukić, Katarina (2019)
In this study, the effects of both ultrasonic bath and probe treatments on the phenolic, chromatic and aroma composition of young red wine Cabernet Sauvignon were studied and modeled by artificial neural networks (ANNs). Moreover, the effect of high power ultrasound (HPU) along with antioxidants addition (sulfur dioxide and glutathione) was investigated during 6 months of aging in bottles. Lower amplitude and temperature, shorter treatment duration and particularly lower frequency showed a more favorable and milder effect on the chemical composition of wine. In the case of the ultrasonic probe treatment, similar effect was achieved primarily by a larger probe diameter as well as lower amplitude and treatment duration. Selected ANN models showed the best predictions for the chromatic characteristics followed by total phenolics and anthocyanins. The changes induced by HPU treatment after 6 months of aging were mainly detected in the composition of phenolic compounds (both total and individual), where higher concentration of antioxidants (sulfur dioxide and glutathione) slowed down the decrease rate of these compounds during aging. However, HPU treatment did not influence most of the chromatic characteristics and aroma compounds, except lightness and fatty acids. The obtained results indicated that suitable ultrasound treatment might accelerate some aging reactions and shorten the period of wine aging.